Unpaid Caring Within and Outside the Carer's Home in England and Wales. Issue 1 (24th January 2012) - Norman, Paul; Purdam, Kingsley
ABSTRACT Unpaid caring is defined as any help or support provided to family members, friends, neighbours, or others because of their long‐term physical or mental health or disability, or problems related to old age. It is estimated that there are over 5.2 million unpaid carers in England and Wales (2001 Census). Using the Small Area Microdata from the 2001 Census Samples of Anonymised Records, we examine geographic and socio‐demographic variations in unpaid caring across England and Wales at local authority level with a particular focus on carers aged 40 years and older, comparing those who provide unpaid care within their own household and outside their household. The distinction between care within and outside the household is based on whether or not the carer lived with a co‐resident reporting a limiting long‐term illness. We find a strong geographical relationship between levels of illness and of unpaid care. However, when this is disaggregated by whether the care is provided within or outside the household, we find that care away from the home is likely to be outside the geographical area in which the carer lives. Our individual level analyses suggest associations between rates of unpaid caring and a person's age, gender, ethnicity, social class, and the carer's own health status. Moreover, these relationships are different for people who provide care within or outside their own household. Our findings have important implications for our understanding of the dynamics of caring and for service providers at a national and local level and also for government focus on independent living for people with social care needs and those in later old age. Unpaid carers who do not live with people they care for are likely to face different demands. Support is needed both for themselves and for the people whom they care. Copyright © 2012 John Wiley & Sons, Ltd.